159k views
5 votes
Still don’t get it idk lol

Still don’t get it idk lol-example-1
User Jure
by
5.2k points

2 Answers

2 votes
first you have to solve for x (below)
(3x-3)-(2x-6)=x+3
if you try plugging in 10 for x you get 2(10)-6=14 + (10)+3=13 = 3(10)-3=27
14+13=27

answer:XQ=14
User Worldofjr
by
4.8k points
2 votes

Answer:

XQ = 12

Explanation:

In this question it asks for XQ instead of x, but you need to find x first.

1. Find x.

XQ is half of MQ so this statement is true: 3x - 3 = 2(2x - 6)

Solve for x.

3x - 3 = 2(2x - 6)

Distribute 2.

3x - 3 = 4x - 12

Isolate x.

3x = 4x - 9

-x = -9

Divide -1 out.

x = 9

Now solve for XQ, which the equation is given.

XQ = 2(9) - 6

XQ = 18 - 6

XQ = 12

User Brrwdl
by
5.6k points